2021
DOI: 10.2147/copd.s321877
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Response Induced by RELMβ Upregulates IL-8 and IL-1β Expression in Bronchial Epithelial Cells in COPD

Abstract: Purpose Chronic obstructive pulmonary disease (COPD) is associated with a complex inflammatory regulatory network. Resistin-like molecule β (RELMβ) is highly expressed in the lungs of COPD patients. We aimed to investigate the proinflammatory effect of RELMβ on airway epithelial cells in COPD. Methods First, a GEO dataset was used to analyze the expression of the RELMβ gene in the COPD and control groups as well as the protein levels of RELMβ in the sera of outpatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…In addition, RELMβ also promotes the expression of the inflammatory factors IL-8 and IL-1β by inducing phosphorylation of p38 MAPK in BECs, which is involved in airway inflammation in chronic obstructive pulmonary disease (COPD) [ 51 ]. After the mice are chronically infected with gastrointestinal (GI) helminth Trichuris muris , the goblet cell-derived RELMβ stimulates TNF-α and IL-6 in macrophages, thereby promoting intestinal inflammation [ 52 ]. The macrophages exposed to RELMβ induce the expression of major histocompatibility complex class II (MHC II) and the secretion of IL-12/23p40, which can increase IFN-γ production by recruiting effector Th1 cells into the inflammatory region [ 52 ].…”
Section: Biological Functions Mediated By Relmsmentioning
confidence: 99%
“…In addition, RELMβ also promotes the expression of the inflammatory factors IL-8 and IL-1β by inducing phosphorylation of p38 MAPK in BECs, which is involved in airway inflammation in chronic obstructive pulmonary disease (COPD) [ 51 ]. After the mice are chronically infected with gastrointestinal (GI) helminth Trichuris muris , the goblet cell-derived RELMβ stimulates TNF-α and IL-6 in macrophages, thereby promoting intestinal inflammation [ 52 ]. The macrophages exposed to RELMβ induce the expression of major histocompatibility complex class II (MHC II) and the secretion of IL-12/23p40, which can increase IFN-γ production by recruiting effector Th1 cells into the inflammatory region [ 52 ].…”
Section: Biological Functions Mediated By Relmsmentioning
confidence: 99%
“…It also confirmed that the expressions of TNF-α and IL-6 were elevated and regulated by the IL-1β pathway. Elevated IL-1β and serum IL-6 expression levels in patients with COPD can activate the IL-1β-system inflammatory axis pathway and pose an increased risk for COPD frequent exacerbators ( 27 , 28 ). The results of this study indicated that after Veillonella parvula treatment, the expressions of IL-1, IL-6, and TNF-α in the cells were elevated markedly, and the expression of p-NF-κB was increased substantially, indicating that Veillonella parvula activated the inflammatory pathway and ultimately destroyed cell viability.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory Response to exogenous and endogenous noxious stimuli and induction of IL-6 and IL-8 secretion by bronchial epithelial cells [14,15].…”
Section: Il-1βmentioning
confidence: 99%
“…Pro-inflammatory Neutrophil recruitment with an important role in pathological and physiological conditions [15,17].…”
Section: Il-8mentioning
confidence: 99%